Infection control of Aeromonas hydrophila in catfish (Clarias sp.) using mixture of meniran Phyllanthus niruri and garlic Allium sativum in feed - Dinamella Wahjuningrum; Eka Hidayatus Solikhah; Tatag Budiardi; Mia Setiawati (Jurnal Akuakultur Indonesia)
Motile aeromonad septicaemia (MAS) is caused by the bacterium Aeromonas hydrophila. The use of plant (natural materials) such as meniran and garlic can be as an alternative way to inhibit the activity of A. hydrophila by their active substances which have potency as an antibacterial and immunostimulant. The aim of this study was to analyze the effectiveness of using a mixture of meniran and garlic in feed to control of A. hydrophila in catfish. There were split in two kind of doses namely, preventive (garlic:meniran=5 ppt:20 ppt) and curative (garlic:meniran=10 ppt:40 ppt). The preventive treatment was given for two weeks before challenging test. The curative treatment was performed on 2th-8th day after challenging test.  Challenging test was carried out by intramuscularly injecting of 0,1 mL A. hydrophila (108cfu/ml)  into the fish. The results indicated that preventive treatment with a mixture of extracts 5 ppt meniran and 20 ppt garlic was more effective in preventing infection of A. hydrophila than curative treatment.